2010
DOI: 10.1242/jeb.037929
|View full text |Cite
|
Sign up to set email alerts
|

Development of aerobic and anaerobic metabolism in cardiac and skeletal muscles from harp and hooded seals

Abstract: SUMMARYIn diving animals, skeletal muscle adaptations to extend underwater time despite selective vasoconstriction include elevated myoglobin (Mb) concentrations, high acid buffering ability () and high aerobic and anaerobic enzyme activities. However, because cardiac muscle is perfused during dives, it may rely less heavily on Mb,  and anaerobic pathways to support contractile activity. In addition, because cardiac tissue must sustain contractile activity even before birth, it may be more physiologically ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 63 publications
2
31
0
1
Order By: Relevance
“…Elephant seal pups also increase their antioxidant defenses at the end of their postweaning fast, suggesting that the activation of the antioxidant system in these mammals is an essential part of their developmental process and prepares them to dive, which is the next step in their life history (Vázquez-Medina et al, 2010;Vázquez-Medina et al, 2011c) suggest that, because apnea stimulates the adaptive response to oxidative stress, and the number and duration of apneas increase with development in elephant seal pups, apnea is essential to prime the seal's antioxidant mechanisms that allow them to cope with the subsequent diving-induced hypoxemia and ischemia/reperfusion/ reoxygenation while at sea. Maturation-related increases in antioxidant capacity have also been documented in the deep-diving hooded seal (Vázquez-Medina et al, 2011a;Vázquez-Medina et al, 2011b), in which oxygen stores (hemoglobin and Mb content), acid buffering capacity, and aerobic and anaerobic enzyme activities also increase with maturation in the skeletal muscle (Burns et al, 2007;Burns et al, 2010;Lestyk et al, 2009). In the present study, repetitive apneas increased Mb expression and HIF-1 nuclear content in the skeletal muscle of elephant seals.…”
Section: Eupneasupporting
confidence: 73%
“…Elephant seal pups also increase their antioxidant defenses at the end of their postweaning fast, suggesting that the activation of the antioxidant system in these mammals is an essential part of their developmental process and prepares them to dive, which is the next step in their life history (Vázquez-Medina et al, 2010;Vázquez-Medina et al, 2011c) suggest that, because apnea stimulates the adaptive response to oxidative stress, and the number and duration of apneas increase with development in elephant seal pups, apnea is essential to prime the seal's antioxidant mechanisms that allow them to cope with the subsequent diving-induced hypoxemia and ischemia/reperfusion/ reoxygenation while at sea. Maturation-related increases in antioxidant capacity have also been documented in the deep-diving hooded seal (Vázquez-Medina et al, 2011a;Vázquez-Medina et al, 2011b), in which oxygen stores (hemoglobin and Mb content), acid buffering capacity, and aerobic and anaerobic enzyme activities also increase with maturation in the skeletal muscle (Burns et al, 2007;Burns et al, 2010;Lestyk et al, 2009). In the present study, repetitive apneas increased Mb expression and HIF-1 nuclear content in the skeletal muscle of elephant seals.…”
Section: Eupneasupporting
confidence: 73%
“…without the cues normally associated with classical myoglobin regulation pathways. This is also true for other seal species, as studies have found that myoglobin concentrations show a trend of increasing from birth to when the animal is weaned (Burns et al, 2010). While myoglobin expression in terrestrial mouse models appears to be regulated by a combination of several stimuli (hypoxia and skeletal muscle contraction), developing seals already express high levels of myoglobin before experiencing the same physiological cues.…”
Section: Introductionmentioning
confidence: 87%
“…This finding may explain why non-diving weaned Weddell seal pups have myoglobin concentrations up to 35mgg -1 wet tissue in their primary swimming muscle (Kanatous et al, 2008). Weaned harp seal (Pagophilus groenlandicus) and hooded seal (Cystophora cristata) pups have ~30% of the myoglobin content of adults in their skeletal muscle while weaned Weddell seal pups specifically have 35.5±3mg myoglobing -1 wet tissue or 63% of that of adults (Burns et al, 2010;Kanatous et al, 2008). During development, seal pups rely on milk with a high fat content (>50%) and a relatively low carbohydrate content as an energy source before commencement of their first breath-hold dive (Burns et al, 2010;Oftedal, 1993).…”
Section: A De Miranda Jr and Othersmentioning
confidence: 99%
“…Moreover, hooded seal pups are physically inactive during the suckling period, which is largely spent suckling or sleeping. Although milk-derived lipids may have stimulated some Mb development (Burns et al, 2010;De Miranda et al, 2012), we do not expect that much liver iron was mobilized for Mb synthesis during lactation, as this period lasts for only about 4days in this species (Bowen et al, 1987). Folkow et al, 2010).…”
Section: Discussionmentioning
confidence: 89%